Assessing algebraic conceptions on functions: An instrument presentation - Mangulabnan, Pauline Anne Therese M. (Animo Repository, 2024)
This is a presentation of two instruments which mathematics educators may use in checking for algebraic conceptions of students. The first instrument focuses on the translation issues of students from algebraic word problems to mathematical equations. The second instrument focuses on the conceptions of students on functions including domain, range and graph. Such instruments may help educators for designing a learning unit and/or assessing learning. The presentation will include the actual instruments, how to use the instruments, and how to interpret the instruments.